NMR Lineshapes and Scalar Relaxation of the Water‐Endofullerene H217O@C60. Issue 3 (9th February 2018) - Elliott, Stuart James; Bengs, Christian; Kouril, Karel; Meier, Benno; Alom, Shamim; Whitby, Richard John; Levitt, Malcolm Harris
Abstract: The 17 O isotopomer of the water‐endofullerene H2 O@C60 displays a remarkable proton NMR spectrum, with six well resolved peaks. These peaks are due to the J ‐coupling between the water protons and the 17 O nucleus, which has spin‐5/2. The resolution of these peaks is enabled by the suppression of water proton exchange by the fullerene cage. The six peaks display an unusual pattern of linewidths, which we model by a Liouville‐space treatment of scalar relaxation due to quadrupolar relaxation of the 17 O nuclei. The data are consistent with rotational diffusion of the water molecules on the sub‐picosecond timescale. Abstract : The 17 O isotopomer of the water‐endofullerene H2 O@C60 displays a remarkable proton NMR spectrum, with six well‐resolved peaks.